2017
DOI: 10.1016/j.cgh.2016.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Advanced-Stage Colorectal Cancer in Persons Younger Than 50 Years Not Associated With Longer Duration of Symptoms or Time to Diagnosis

Abstract: Background & Aims The incidence of colorectal cancer (CRC) is increasing in the United States (US) among adults under the age of 50 years. Studies of young-onset CRC have focused on outcomes and treatment patterns. We examined patient presentation, provider evaluation, and time to diagnosis, which can affect stage and prognosis. Methods In a retrospective study, we collected data from patients with a diagnosis of colorectal adenocarcinoma, confirmed by pathologists, seen at the Stanford Cancer Institute from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
229
3
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(253 citation statements)
references
References 31 publications
17
229
3
4
Order By: Relevance
“…The underlying causes for the increased incidence of early‐onset CRC are not fully understood, but recognized risk factors may play an important role. A higher fraction of individuals with early‐onset disease has a family history of CRC or a risk‐inducing genetic mutation compared with adults aged 50 years and older . Several other known CRC risk factors also are likely contributing to early‐onset disease, including increasing trends in obesity, the prevalence of type II diabetes mellitus, and a sedentary lifestyle.…”
Section: Screening and Surveillance For The Early Detection Of Adenommentioning
confidence: 99%
See 2 more Smart Citations
“…The underlying causes for the increased incidence of early‐onset CRC are not fully understood, but recognized risk factors may play an important role. A higher fraction of individuals with early‐onset disease has a family history of CRC or a risk‐inducing genetic mutation compared with adults aged 50 years and older . Several other known CRC risk factors also are likely contributing to early‐onset disease, including increasing trends in obesity, the prevalence of type II diabetes mellitus, and a sedentary lifestyle.…”
Section: Screening and Surveillance For The Early Detection Of Adenommentioning
confidence: 99%
“…Delay in diagnosis is a common and concerning feature of young‐onset CRC. One study indicated that the median time to initial clinical presentation after the onset of symptoms was twice as long for patients with early‐onset CRC compared with older patients (60 days vs 30 days), and that patients with early‐onset CRC experienced a longer time to diagnosis after symptom recognition (128 days vs 79 days) . A study of patients with rectal cancer indicated that the time from symptom onset to treatment was more than 4 times longer for patients younger than 50 years (217 days) compared with adults aged 50 years and older (58 days) .…”
Section: Screening and Surveillance For The Early Detection Of Adenommentioning
confidence: 99%
See 1 more Smart Citation
“…Delay in diagnosis is another common and concerning feature of young‐onset CRC. One study found that the median time for initial clinical presentation after the onset of symptoms was twice as long for patients with young‐onset CRC compared with older patients (60 days vs 30 days) and that patients with young‐onset CRC experienced a longer time to diagnosis after symptom recognition (128 days vs 79 days) . A study of patients with rectal cancer found that the time from symptom onset to treatment was more than 4 times longer for patients younger than 50 years (217 days) compared with adults aged 50 years and older (58 days) .…”
Section: Screening and Surveillance For The Early Detection Of Adenommentioning
confidence: 99%
“…7 This study's aims are to determine the fractions of young-onset CRC patients in the same cohort who had recognized risk factors for early CRC, as a function of age by decade. It is hypothesized that only a minority at all ages would qualify for early screening based on existing recommendations.…”
Section: Introductionmentioning
confidence: 99%